1970
DOI: 10.1139/v70-048
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the pyrolysis of propylene. Part I

Abstract: The kinetics of the pyrolysis of propylene have been studied over the temperature range 743-873 "K and the pressure range 200-600 Torr. At the lower temperatures initiai rates of formation of methane, propane, and C , products were measured and shown to be formed by a radical process of very short chain length. The orders and activation energies of the rates were consistent mith the occurrence of the bimolecular initiation step 2C3Hcj -t C3Hs + C3H7 Measurement of the pressure change showed that products of ~n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1970
1970
1986
1986

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…In the pyrolysis of propylene, for example, the products of the ene reaction, hexene-1 and 4-methylpentene-1, are major products and may contribute to secondary initiation. There are other major primacy c 6 products, however, formed by radial processes [20] which could be equally important in supplying secondary initiation. In the propylene pyrolysis the processes of primary and secondary initiation have not been well-defined at all temperatures.…”
Section: Formation Of Cyclopentene and 1 -Methylcyclopentenementioning
confidence: 99%
“…In the pyrolysis of propylene, for example, the products of the ene reaction, hexene-1 and 4-methylpentene-1, are major products and may contribute to secondary initiation. There are other major primacy c 6 products, however, formed by radial processes [20] which could be equally important in supplying secondary initiation. In the propylene pyrolysis the processes of primary and secondary initiation have not been well-defined at all temperatures.…”
Section: Formation Of Cyclopentene and 1 -Methylcyclopentenementioning
confidence: 99%
“…In Table 2, the rates of formation of the main products from mixtures of propylene and acetaldehyde in the ratio 0.07 are compared with the rates of formation of each of these products from the pyrolysis of acetaldehyde (21) and propylene (13) separately. The rates of formation of products from the pyrolysis of 40 Torr of propylene were not measured directly, but were obtained by extrapolation of rates measured at higher pressures (100-600 Torr).…”
Section: Resultsmentioning
confidence: 99%
“…The bimolecular reaction of propylene to give radicals, either with itself or with the reactant, has not been considered in inhibition studies, but may under some conditions be faster than the unimolecular dissociation (13).…”
Section: Introductionmentioning
confidence: 99%
“…This covers the range of several studies, but this product was not detected [2,[16][17][18]. Most of the analyses in these studies were done at pressures of 100 or 200 torr, and since the equilibrium concentration and the rate depend on the square of the concentration of propylene, the yields of 1,2-dimethylcyclobutane would be barely detectable at the lower pressures.…”
Section: B Propylenementioning
confidence: 99%
“…Recent studies of the thermal reactions of ethylene [I] and propylene [2] have shown that in each case initiation occurs by the respective bimolecular reactions :…”
Section: Introductionmentioning
confidence: 99%